2007
DOI: 10.1007/s11458-007-0066-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro investigation on cinnabar dissolution

Abstract: To study the effects of different chemical factors in the gastrointestinal tract, i.e. pH, proteins, amino acids, ionic strength and Na 2 S, on the dissolution of cinnabar. The content of the total mercury in various dissolutions of cinnabar was analyzed by UV/VIS Spectrophotometer. Laser Particle Size Analyzer measured the particle distributions in the dissolution of cinnabar. The chemical species of dissolved substance of cinnabar in the presence of Na 2 S were determined using ESI-MS. The results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
1
10
1
Order By: Relevance
“…2A) indicates the existence of hydroxyl groups. Therefore, the essential component of dissolved components from cinnabar in a low concentration of Na 2 S solution appeared to be HgS 2 (OH) − , which is consistent with our previous electrospray ionization-mass spectrometry (ESI-MS) data (Zeng et al, 2007).…”
Section: Composition Of Dissoluble Substance Of Cinnabarsupporting
confidence: 91%
See 3 more Smart Citations
“…2A) indicates the existence of hydroxyl groups. Therefore, the essential component of dissolved components from cinnabar in a low concentration of Na 2 S solution appeared to be HgS 2 (OH) − , which is consistent with our previous electrospray ionization-mass spectrometry (ESI-MS) data (Zeng et al, 2007).…”
Section: Composition Of Dissoluble Substance Of Cinnabarsupporting
confidence: 91%
“…Our previous results on cinnabar dissolution (Zeng et al, 2007) have suggested that the small intestinal tract is unlikely the place for cinnabar dissolution because amino acids and proteins (e.g. pepsin, trypsin and BSA) have no effects on dissolution of cinnabar; while cinnabar exhibited favorable solubility in simulate gastric acid and sulfur-rich intestinal fluids.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Hg-cysteine) modulates the efficiency of the microbial methylation of mercury (Schaefer and Morel, 2009;Sparling, 2009). Since HgS can hardly release mercury ions (lg K sp = −52.03) in water or cysteine solution (Zeng et al, 2007), it is unfavorable for microbial conversion of cinnabar to form methylation (Choi and Bartha, 1993;Choi et al, 1994a,b). In fact, Robinson and Tuovinen (1984) have indicated that because of the low redox potential, MeHg was not formed from HgS by cultures of Clostridium cochlearium or by chemical methylation with methylcobalamin under anaerobic conditions; albeit in aerobic organic sediments, MeHg was produced from cinnabar at much lower rates than that from HgCl 2 .…”
Section: Introductionmentioning
confidence: 99%